NOVEMBER 2013 PLACEMENT ADS (The Accounting Review, 2013)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.DONGBEI UNIVERSITY OF FINANCE AND ECONOMICS (DUFE), School of Accounting invites Ph.D. graduates of overseas universities to work as a full-time teacher or researcher. This is a research-oriented position. Job description: Job duties for a successful applicant will include research, teaching (which is not required if applying for a researcher position), and service to the School and the University as a full-time staff. Benefits: The annual salary will be U.S.$60,000 or more, plus health insurance, housing accumulation funds, temporary housing (or housing allowances), traveling expenses for international conferences, research grant, and Ph.D. allowance. Rank, extra awards, and funds will be granted depending on research experience and performance. Additionally, a private office and necessary research resources are available. JOB QUALIFICATIONS: Candidates must have a completed Ph.D. degree in accounting or corporate finance from an overseas university and concentrate on the research in accounting, auditing, or corporate finance. Contact Qi Yuan, qiyuan@dufe.edu.cnNORTHEASTERN UNIVERSITY is seeking applications for tenured or tenure-track positions at the Assistant or Associate Professor rank effective for the 2014–2015 academic year; the earliest start date will be July 1, 2014. Candidates must have a doctorate degree in accounting or a closely related business field by the start date and be committed to excellence in research and teaching. The Accounting Group at Northeastern is nationally recognized for its high-quality behavioral accounting research focused on auditing, governance, tax, and managerial and ethical judgment and decision making. We provide a supportive environment where collaboration in research and teaching is encouraged. The position offers competitive compensation and teaching responsibilities that enable a significant level of high-impact research. Rank and salary are dependent on qualifications. Summer funding, graduate assistants, and travel support are available. Accounting courses are offered at both the undergraduate and at the graduate levels (M.B.A., M.S./M.B.A., M.S.A., and M.S. Tax). For optimal consideration, submit your cover letter, cv, and two samples of scholarly work by July 26 through to: http://www.cba.neu.edu/faculty/ (click on “Faculty Positions” link on the right-hand side). Northeastern University is an Affirmative Action/Equal Opportunity/Title IX Employer and welcomes applications from minorities, women, and disabled persons.UNIVERSITY OF CINCINNATI, Lindner College of Business invites applicants for Full Professor of Accounting beginning Fall 2014. Candidates must have a doctorate in accounting from an AACSB-accredited institution, with consistent research productivity, including recent quality, refereed publications. Academic qualifications must be commensurate with tenure at a business doctoral-granting institution. A demonstrated ability to work with other faculty on research projects is valued. Primary responsibilities include mentoring others in developing their research agenda and publishing in peer-reviewed journals. Excellent teaching credentials are highly valued and quality teaching is expected; teaching load is commensurate with research productivity. Significant public or private accounting experience is valued, but not required, as are professional accounting certifications. Candidates must possess both written and spoken English fluency. To apply for position (213UC5233), please see http://www.jobsatuc.com. For questions, contact Robert.Larson@uc.edu. UC is an Affirmative Action/Equal Opportunity Employer and is a smoke-free work environment.UNIVERSITY OF SOUTH CAROLINA, School of Accounting is accepting applications for two tenure-track positions open at all ranks in the area of beginning Fall 2014. Candidates should possess a doctorate or to their doctorate by 2014. Ph.D. should the for teaching excellence and publishing in journals. Candidates for an rank should have a of teaching excellence and publishing in journals. For an in international is are competitive and commensurate with experience and faculty are to the of or a to: Professor School of University of The University of is an and are to OF School of and is accepting applications for a tenure-track position or to 2014. Candidates should a degree in accounting (or be in an or a degree and will be to with a in tax, but all are to is valued. Candidates should have and be in with include undergraduate and graduate commensurate with of an institution, and service to the University and Position is the required faculty and a of of teaching and the and of Review of applications will and the position is to the and are to UNIVERSITY OF School of Accounting in the College of Business and is seeking applicants for a tenure-track position for the 2014–2015 academic is on include in related and with all and University include undergraduate Ph.D. in accounting is highly are will be professional and teaching experience are are in and other accounting at or OF School of Accounting invites applications for Professor positions beginning Fall 2014. Candidates for Assistant Professor should possess a Ph.D. in accounting from an AACSB-accredited will be and research including the ability to in accounting journals. Candidates for Associate Professor must tenure as by in accounting and demonstrated excellence in teaching. research and teaching are to teaching is should submit a a research for at a the and contact information of and of teaching ability to: School of University of of School of Business and invites applications for a tenure-track faculty position in 2014. of and rank are job developing and teaching undergraduate and graduate accounting courses in both and and mentoring an research agenda that to in nationally or recognized quality journals. to the and University is qualifications a Ph.D. in of teaching of the ability to in accounting journals. must be should a of a that of teaching experience and research of will the position is the position be to at University is a university with undergraduate and graduate The School of Business is University a to the and of the university and that School of Business graduate of a faculty in accounting the academic We are open to all levels of Assistant Associate or Full We will be at the must have a Ph.D. or be of a degree in accounting or a related We applications to be by We will research of quality that will have on the must be that the research and at a level of quality consistent with We are interested in with others and the environment of the The School of in is the business The Accounting and applications and all must be by to: in the of the that are applying for an accounting position. College is an and are to College of Business invites applications for a tenure-track Assistant Professor position in the of to 2014. will be applicants must be and should have a to teaching and include teaching undergraduate and graduate in of will be The College of Business and the of are both by To please and submit your University is an OF applicants for two faculty positions in undergraduate courses in Accounting and Business courses to the scholarly and on and University qualifications include a Ph.D. in Accounting or a degree in a closely related field in qualifications for the position are an with or an M.S. in Accounting with experience in a relevant or is The must an ability to at the university level and in scholarly in relevant professional and public is with and the for position and how to will a of School of Business invites applications for a tenure-track position at the Assistant or Associate Professor The successful will undergraduate and graduate in the area of Accounting The will be to scholarly research in a environment that welcomes and as as and University is the The School of by the will be its Business in July Accounting and from the for Accounting The of Accounting offers two a in Accounting and a in Accounting for qualifications. graduates are highly by and other The and have a to faculty and and applications from of Review of applications will and the position is The position is to with the Fall must the required doctorate in accounting or related field by the of demonstrated excellence in teaching and to work closely with in and including professional research and an or research Accounting and prior professional accounting experience are be For information please contact the at or OF CINCINNATI, Lindner College of Business invites applicants for two tenure-track Assistant or Associate Accounting Professor beginning Fall 2014. Candidates must have a doctorate in accounting from an AACSB-accredited institution, with consistent research productivity, including recent quality, refereed publications. graduates and with by July must the ability to quality research and must be a Excellent teaching credentials are highly valued and quality teaching is expected; teaching load is commensurate with research productivity. Significant public or private accounting experience is highly valued, but not required, as are professional accounting certifications. Candidates must possess both written and spoken English fluency. To apply for position please go to: http://www.jobsatuc.com. For questions, contact Robert.Larson@uc.edu. UC is an Affirmative Action/Equal Opportunity Employer and is a smoke-free work School of Business invites applications for tenured and faculty positions in accounting, effective 1, from at all levels and of their are interested in accounting, managerial accounting, tax, and other Candidates should have or to a Ph.D. by 1, and should possess a and research The successful will be to research and to both and Ph.D. courses in should include and of research publications. are to submit their applications by to research and and teaching if all be by to or by to: of School of and for For an application to be all applicants must have of to the or The application deadline is 1, University is an Opportunity Employer and is committed to the of its welcomes of and applications from and of as as others of to the research, and and School of Business invites applications for the of the and in Business a tenure-track position beginning 2014. A Ph.D. in business business or closely related a for and of excellence in and research with a are The will business at the undergraduate and graduate levels and business and and to in related to business and the will and to business and faculty the of ethical and in business or will be an in business and be a in international business Candidates should a of and of all in to: For or of completed applications will 1, and will the position is is an Affirmative Action/Equal Opportunity The University is committed to in the and applications from and UNIVERSITY OF is an beginning or work with and have experience with a of teaching and include and and for and and to and will undergraduate and graduate accounting will be in research. are and is on research. will be to related to or other We our faculty to be in their field and to high-quality teaching and research faculty are to on the service the of both the and College and to their Assistant are to have completed their degree the have not completed will be but at the rank of Associate are to have an of high-quality research and the is on research. with a of quality teaching will be OF a tenure-track position as or Full Professor of Accounting available 2014. The will have an in teaching Accounting are seeking a of responsibilities will a work environment at The College of Business is AACSB-accredited and offers of through with and The of Accounting of faculty undergraduate and of Accounting is in the an in with a of Candidates must apply are For more information please Accounting OF invites applications for a tenure-track position at the Assistant or Associate Professor level in 2014–2015 academic College of is in the and The faculty will accounting courses at the undergraduate graduate Candidates should a degree in accounting or related Candidates should teaching will be to with work experience in accounting and related Candidates should have an in research and must have demonstrated the to and quality research in peer-reviewed academic journals. Candidates should submit a of a and the of academic submit application and to applicants submit their applications Business School invites applications for positions in accounting at all levels and Full from the academic ranks will be must have a doctorate degree in accounting or related by 2014. We for applicants from all of University is a and research-oriented university in the of and The Business School of University on its of business which to the of Business in offers undergraduate and that cover of business and as as professional including of auditing, and of We competitive compensation that include research funds, and housing To please submit a of research and to Professor OF invites applications for a position at the Assistant or Associate Professor level in College of is in the and The faculty will accounting courses at the undergraduate graduate Candidates should a degree in accounting or in a related Candidates should teaching will be to with work experience in accounting and related Candidates should have an in research and must have demonstrated the to and quality research in peer-reviewed academic journals. Candidates should submit a of a and the of academic submit application and to applicants submit their applications School of Accounting is information for two faculty The will have a Ph.D. in We with a and with significant scholarly The two teaching are in accounting and a in and accounting with a in teaching and research in the area of and accounting are to an information To a contact School of applicants for a tenure-track faculty position in Accounting for Fall 2014. is a must have a Ph.D. (or in Accounting from an or will a Ph.D. by 1, and have an in research and teaching in or Candidates should be to at the undergraduate or graduate and teaching are on qualifications and should of and of teaching to the Accounting must be by but will be the position is is an Action/Equal Opportunity/Title IX School of Business invites applications for a tenure-track position in in undergraduate or a of undergraduate and graduate for in quality business research with an of undergraduate in and to with and in the in a business from an and a in a doctorate in or plus graduate with a business ability and to business with in and This is a tenure-track position. OF invites applications for a tenure-track the Assistant or Associate Professor or faculty position in of and in the 2014–2015 academic The faculty will accounting courses at the undergraduate graduate at College of include courses at its in and include teaching at in and Candidates should a degree in accounting or related Candidates should teaching our teaching are in the of tax, and interested in all teaching will be will be to with work experience in accounting and related Candidates should have an in research and publication and must have demonstrated the to and quality research in peer-reviewed academic journals. must the ability to and a and apply a cover that how the qualifications and are to support the of the submit a of teaching a of research and contact information for To submit of please Professor of the or College of We support excellence and are committed to a and for is an Opportunity School of an AACSB-accredited applicants for a tenure-track position in Accounting beginning in Fall 2014. Rank will be commensurate with qualifications. Candidates must have a Ph.D. or in Accounting or in a related a degree will be as Candidates must provide of teaching and research include teaching undergraduate and graduate courses in Accounting and in scholarly and in The with in tax, auditing, and accounting but all are to should a of of teaching a of research, and of should be to Accounting will and the position is College is an in the in the section of We our and to be about our and to a to that and are to We are committed to Employer UNIVERSITY OF School of Accounting faculty for the and and competitive on 1, 2014. Ph.D. in accounting or or of Accounting and professional Candidates must be and to at both the undergraduate and graduate including Candidates must possess prior teaching experience and provide of quality teaching performance. will be on of quality and to teaching are to submit a and of teaching qualifications to: School of College of University of For contact the of the School of The of applications will will be the position is The University of is an and are to of Accounting and is accepting applications for a tenure-track position at the Assistant Professor level beginning Fall 2014. degree from an AACSB-accredited in the Accounting or a closely related (or teaching and a research agenda in accounting are of scholarly research in accounting (or related is required and the to provide in the and University is with a with a (or and M.S. in or M.S. in or in are to will be for the of is required at the of 2014. include teaching courses in the undergraduate graduate will be to with a in tax, but all including and are to a of effective in including and in an of that and professional and an ability to work with from an in the and of the institution. For more information the for the and the of the successful if not a must have from the of and to work in the will be to applications by November 1, and will position is should submit a of with contact and a of application that and the qualifications and responsibilities in the position and applications to: of Accounting and College of Business and is an AND of Accounting and College of Business to or more tenure-track positions to 2014. will be to at the Assistant or Associate Professor The for with teaching and research in with in other and ranks will be will have a Ph.D. in accounting from an AACSB-accredited a of scholarly research consistent with the rank and at both undergraduate and graduate about the and its is available must apply and include with the application a cover letter, and of or and contact information of Review of applications will 1, and are should be to: Professor or Professor of the or Professor is an School of School of Accounting invites applications for two tenure-track positions beginning Fall at the Assistant Professor of research and teaching will be must have an doctorate in applicants must have a to The position is on the but applicants be to on the will and will the position is will in the Fall positions are available A of and a of teaching should be to: School of Business University is an Affirmative Action/Equal Employer committed to is a School of Business and invites applications for a tenure-track Assistant Professor of Accounting effective Fall This position offers a competitive salary and a research as as a research The teaching load is the and courses through the tenure must have a degree or be and the for publishing high-quality academic research and teaching. The successful will be to as a by the is of the School of Business and and nationally recognized and in and research to a of in accounting and in the of offers undergraduate in the and and and graduate The School is by and offers in business and accounting as as an The School and graduate in a information be should submit a cover letter, including at and a research to in the University is an Opportunity committed to to all to or University for all OF College of School of invites applications for an Professor to courses the academic in the of or accounting and research in Candidates should possess a doctorate in Accounting or closely related will be but must be completed of the with Candidates must teaching and of faculty qualifications UNIVERSITY OF College of School of invites applications for a tenure-track at the Assistant Professor level beginning 2014. Candidates should have an doctorate the start of the and the for research in accounting and excellence in teaching. with research and teaching excellence are to The faculty to and accounting The faculty will have the ability to work with and will in and service We applications in all of accounting research and teaching. teaching are in accounting information and managerial is of will applications will be Candidates will be required to submit a and a applications are of scholarly and a of The University of is an Opportunity and are to OF Accounting and School of Business invites applications for faculty position beginning 2014. faculty are to should have a Ph.D. in accounting or relevant in academic and teaching and service (or the in managerial accounting and auditing, all will be Rank will be commensurate with experience and scholarly For applications must be with a or job and of teaching ability by The University of College to a of and will not or applicant of or or UNIVERSITY OF School of Business is seeking to to tenure-track positions in Accounting that in the 2014–2015 academic are from have a Ph.D. (or or to a doctorate in the of our faculty are to research of quality, to and to in and to the academic will be on and will on the of should submit a a of written and the of at two and to the and for research and teaching. will be We will start applications on November and to your application by We will to applications 2014. The University of is an Affirmative Action/Equal Opportunity of Accounting invites applications for or more tenure-track date is 2014. with research and teaching will be Rank is Assistant Professor should be to of a Ph.D. in accounting and for research in high-quality research and effective teaching. Associate and Full Professor must have a Ph.D. in accounting, a of effective and an of in high-quality research that is consistent with are to should submit their at and or contact information for by to OF of and College of Business invites applications for tenure-track at all ranks for Fall 2014. for positions should have a for and a of excellence in teaching at the undergraduate and graduate for positions must have a degree prior to date and for and to excellence in research and teaching. We are seeking applications in all of The College of Business and the are are To be interested applicants should submit the of teaching and research and of with contact information to: of and University of College of Review of applications will and applications will be the position is For a of the position and of the application please To more about College of of and please our website The University of is an minorities, and with are to of Accounting invites applications for a tenure-track beginning Fall 2014. for or Professor will be in all of or are should possess the and ability to be and doctorate in accounting or a closely related field prior to 2014. research and a of successful teaching will be at the Associate and Professor in accounting or closely related field completed by 2014. to high-quality accounting research and to the applicants for Associate or Full Professor must University for at including in refereed accounting or closely related and demonstrated ability as a successful for Full Professor must have a in To consideration, applications must be by November applications will be the position is will be at to submit a of which include a of teaching and research and the and contact information for is an UNIVERSITY OF is seeking applicants for an position to Fall 2014. Job duties include mentoring and and high-impact accounting research, teaching undergraduate and graduate and academic and professional Candidates should a Ph.D. in have an of scholarly research and an of teaching and a of of an and accounting experience are highly Review of applications will and applications by will be should submit their cv, the and of at academic demonstrated of excellence in research and and or to Professor UNIVERSITY OF applicants for a tenure-track position at the Assistant Professor level in all of accounting, with a for to 2014. Candidates should have a Ph.D. in Accounting (or be in the of their and for and to excellence in research and teaching. and accounting experience are highly Review of applications will and applications by are of should submit their of or teaching and of to Professor UNIVERSITY OF School of Accounting and applicants for a tenure-track or tenured position in the area of beginning 2014. are for research, and service at a teaching responsibilities are academic teaching are available for Assistant This position is at the or Full Professor should be focused on publication in the highly journals. Job Candidates for a tenured position should have a of in teaching and research to an of an high-quality research and the and ability to work with Candidates for a tenure-track position should have of high-quality research and teaching A Ph.D. in accounting must be completed by the Rank and salary are competitive and commensurate with qualifications. Summer funding, graduate assistants, and travel support are available. The Accounting offers at the and is by the For information about the School and its faculty and For questions, of or to application School of University of will a of and a cv, of scholarly and the and contact information for at To apply please faculty and with will and will the position is The University of on the of as a and information in the and The to the of the of Opportunity and Accounting Business School is for applicants for positions at the or Full Professor ranks for a tenured or tenure-track position beginning July should have a Ph.D. degree from an or to their degree the applicants must have a research and and the ability and to high-quality research. Associate and Full Professor applicants should have a of and service in to in our application November for information about this position and to submit your 2014. University is an UNIVERSITY is seeking for a full-time Accounting Professor to undergraduate and graduate accounting is commensurate with and The start date for this position is 2014. University applicants have an Ph.D. in Accounting or Ph.D. in a related with graduate in accounting and and demonstrated excellence in teaching both and at both the undergraduate and graduate experience is responsibilities include teaching at both the and as as a to the and work experience in public accounting, or is desired the accounting is to for placement in the A on accounting is professional include research and and in accounting responsibilities of the position include University and a and of accounting and as of the accounting faculty to work with and are the and the OF Accounting of the School of is seeking to positions in the 2014–2015 academic the of research and teaching Candidates must have a Ph.D. degree (or or to the Ph.D. by 2014. apply include an of their of research, a of of and a job be in or The School at is an Affirmative Action/Equal Opportunity Employer with a to the of its and OF School of of Accounting invites applications for a tenure-track position in rank depending qualifications and and consistent with School and University applicants must possess a degree in accounting or a related field (or be to and must have a to accounting research and teaching. for an Associate or Full Professor position must have demonstrated excellence in teaching and an of in academic commensurate with the rank are Review of applications and will the position is should include a samples of recent research of teaching quality, and at two of should be to: of Accounting School of The University of is an Opportunity and OF invites applications for an Assistant Professor position for Fall 2014. will be to with teaching in of auditing, or Candidates must have a Ph.D. with an accounting professional as is is and The offers the undergraduate accounting degree and two in Accounting and M.S. in with about The accounting at both the graduate and undergraduate Candidates should a to: Professor of College of Business University of The University of is an Affirmative Action/Equal Opportunity minorities, and with are to